Association of school hours with outcomes of out-of-hospital cardiac arrest in schoolchildren. Issue 2 (19th August 2019) - Yamashita, Akira; Kurosaki, Hisanori; Takada, Kohei; Tanaka, Yoshio; Hamada, Yoshitaka; Ishita, Tetsuya; Kubo, Minoru; Inaba, Hideo
Abstract : Objective: To investigate the association of school hours with outcomes of schoolchildren with out-of-hospital cardiac arrest (OHCA). Methods: From the 2005–2014 nationwide databases, we extracted the data for 1660 schoolchildren (6–17 years) with bystander-witnessed OHCA. Univariate analyses followed by propensity-matching procedures and stepwise logistic regression analyses were applied. School hours were defined as 08:00 to 18:00. Results: The neurologically favourable 1-month survival rate during school hours was better than that during non-school hours only on school days: 18.4% and 10.5%, respectively. During school hours on school days, patients with OHCA more frequently received bystander cardiopulmonary resuscitation (CPR) and public access defibrillation (PAD), and had a shockable initial rhythm and presumed cardiac aetiology. The neurologically favourable 1-month survival rate did not significantly differ between school hours on school days and all other times of day after propensity score matching: 16.4% vs 16.1% (unadjusted OR 1.02; 95% CI 0.69 to 1.51). Stepwise logistic regression analysis during school hours on school days revealed that shockable initial rhythm (adjusted OR 2.44; 95% CI 1.12 to 5.42), PAD (adjusted OR 3.32; 95% CI 1.23 to 9.10), non-exogenous causes (adjusted OR 5.88; 95% CI 1.85 to 20.0) and a shorter emergency medical service (EMS) response time (adjusted OR 1.15; 95% CI 1.02 to 1.32) and witness-to-first CPR interval (adjusted OR 1.08; 95% CI 1.01 to 1.15) were major factors associated with an improved neurologically favourable 1-month survival rate. Conclusions: School hours are not an independent factor associated with improved outcomes of OHCA in schoolchildren. The time delays in CPR and EMS arrival were independently associated with poor outcomes during school hours on school days.